Pediatric laryngoscopy and bronchoscopy during the COVID-19 pandemic: A four-center collaborative protocol to improve safety with perioperative management strategies and creation of a surgical tent with disposable drapes. (July 2020) - Francom, Christian R.; Javia, Luv R.; Wolter, Nikolaus E.; Lee, Gi Soo; Wine, Todd; Morrissey, Tyler; Papsin, Blake C.; Peyton, James M.; Matava, Clyde T.; Volk, Mark S.; Prager, Jeremy D.; Propst, Evan J.
Abstract: Aerosolization procedures during the COVID-19 pandemic place all operating room personnel at risk for exposure. We offer detailed perioperative management strategies and present a specific protocol designed to improve safety during pediatric laryngoscopy and bronchoscopy. Several methods of using disposable drapes for various procedures are described, with the goal of constructing a tent around the patient to decrease widespread contamination of dispersed droplets and generated aerosol. The concepts presented herein are translatable to future situations where aerosol generating procedures increase risk for any pathogenic exposure. This protocol is a collaborative effort based on knowledge gleaned from clinical and simulation experience from Children's Hospital Colorado, Children's Hospital of Philadelphia, The Hospital for Sick Children in Toronto, and Boston Children's Hospital.